P‐133: Improved Stability of Organic TFTs by Polydimethylsiloxane Passivation. Issue 1 (30th May 2018) - Li, Xiuling; Jeon, Jaekwon; Choi, Jonghyun; He, Mingqian; Manley, Robert; Chang, Jaemyung; Zhelev, Nikolay; Mehrotra, Karan; Jang, Jin
Abstract : The stability of organic TFTs (OTFTs) under bias stress and 85% humidity ambient are improved by polydimethylsiloxane passivation. The passivated OTFTs show a field‐effect mobility (µFE ) of ~1 cm 2 /V . s and on‐to‐off current ratio of ~10 7 . The high performance and excellent stability of the proposed OTFT, make it a promising candidate for future flexible/wearable electronics.